Indonesian National Army Information Centre’s Public Relations Communication Strategy - Nugroho, Lidia Nur Ardelia; Astuti, Sri Wahyuning (Program Studi Ilmu Komunikasi FBIK Unissula, 2024)
The rise of negative news involving Indonesian National Army members has caused a decline in the image of the TNI. One of the issues that is of concern to the community today is the bad actions carried out by unscrupulous members of the Indonesian National Army in various regions. The use of the Instagram social media platform by the Indonesian National Army Information Centre is considered an effort to improve the image of Indonesian National Army agencies. The purpose of this study is to understand how Indonesian National Army Information Centre identifies specific problems or challenges in its efforts to build and maintain a positive image of the Indonesian National Army on Instagram. The research method used was qualitative, involving three people from the internal Indonesian National Army Information Centre in the field of Information and Internet, one lecturer who is an expert in the field of public relations, and three followers of the Indonesian National Army Information Centre’s Instagram account as external informants, two of whom is Indonesian National Army Information Centre’s staff. The results showed that the Indonesian National Army Information Centre had followed several stages proposed by Cutlip, Centre and Broom. However, in terms of activities on social media, especially Instagram, it still needs to be improved because the content is considered less varied and the way the Indonesian National Army conveys information and interacts with the public on Instagram still seems rigid.